2010
DOI: 10.1021/jf102934u
|View full text |Cite
|
Sign up to set email alerts
|

Lycopene Degradation and Isomerization Kinetics during Thermal Processing of an Olive Oil/Tomato Emulsion

Abstract: The stability of lycopene in an olive oil/tomato emulsion during thermal processing (80-140 °C) was studied. Initially, the degradation of total lycopene (all-E plus Z-forms) occurred quickly at temperatures above 100 °C. However, a nonzero plateau value, depending on the processing temperature, was attained after longer treatment times. Besides degradation, the isomerization of total-Z-lycopene as well as the individual isomerization of all-E-, 5-Z-, 9-Z-, and 13-Z-lycopene was studied in detail. After prolon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
53
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 31 publications
12
53
0
Order By: Relevance
“…As stated before, lycopene is normally quite thermostable, but the oil in the tomato puree probably makes lycopene more sensitive to isomerization. Similar to the present results, Colle et al (2010a) also found a remarkable increase in 13-cis-lycopene concentration after a thermal treatment of a tomato puree with 5% olive oil during 10 min at 90°C whereas the change in the other isomers was less pronounced.…”
supporting
confidence: 93%
See 2 more Smart Citations
“…As stated before, lycopene is normally quite thermostable, but the oil in the tomato puree probably makes lycopene more sensitive to isomerization. Similar to the present results, Colle et al (2010a) also found a remarkable increase in 13-cis-lycopene concentration after a thermal treatment of a tomato puree with 5% olive oil during 10 min at 90°C whereas the change in the other isomers was less pronounced.…”
supporting
confidence: 93%
“…Crystalline lycopene can be solubilized in the oil which makes it more susceptible to degradation. At temperatures above 100°C, Colle et al (2010a) also observed oxidative degradation of lycopene during thermal processing of an olive oil/tomato emulsion.…”
Section: Effect On Total Lycopene Concentrationmentioning
confidence: 86%
See 1 more Smart Citation
“…The activation energy in this work was found higher than lycopene from tomato olioresine (11.5 -15 kcal/mole) (Hackett et al, 2004). Furthermore the activation energy of all-trans lycopene degradation was reported as 14.5 kcal/mol for standard lycopene (Lee and Chen, 2002), 6.7 kcal/ mole in olive oil-tomato emulsion (Colle et al, 2010) and 19.8 kcal/mol in safflower oil (Henry et al, 1998). Generally, the degradation of lycopene is high with an increase in temperature and treatment time, particularly when the temperature is above 100C.…”
Section: Temperature Stability Of Vitamin C and Lycopenementioning
confidence: 78%
“…Oxidation may also take place by the action of lipoxygenase, with the formation of hydroperoxides, and the presence of some antioxidants may inhibit this reaction. These processes may be reduced by using techniques that avoid contact with oxygen in air, such as freeze-drying, microwave, or others [25,26,[52][53][54][55][56][57][58].…”
Section: Sources Of Lycopenementioning
confidence: 99%